(untitled) (MEDIEVAL HISTORY OF CENTRAL EURASIA, 2024)
Abstract. The article considers ancient and medieval sources on the Golden Horde and Central Asian history, including information of the ancient authors on peoples of Central Asia, medieval sources, autochthonous sources, Muslim historiography. The article is dedicated also to the observation of history and ethnography of Kazakhs (mostly in Western oriental studies). A separate section reviews the phenomenon of nomadism in the context of such scientific problems as geographic factor and natural environment, social structure, political system and nomadic culture including the Kazakhs. In this context, the book presents western opinions regarding the following issues: impact of the Golden Horde onto Eurasia, a role of the Kipchaks within this area, Islamic and Turkic studies.